Books of occurrences: Violence and indiscipline in state managed schools - Claudia Lemos Vóvio; Vanda Mendes Ribeiro; Luiz Carlos Novaes; Maria Helena Bravo (Arizona State University, 2016)
This article suggests categories for the analysis of registries made in books of occurrences within state managed schools. Furthermore it verifies the categories' pertinence for the comprehension of schooling environment in these institutions. In a context of vulnerable territories in which these institutions are set, violence and indiscipline are considered relevant to grasp what goes on in their midst. The document basis counts seven such books in each school, produced between 2007 and 2013. A significant difference between schools springs up, both in terms of quantity of registries and in terms of categories distribution. Bearing in mind these differences and the weight of external factors on each school environment, both frequently notify events that threaten the physical and moral integrity of students, which, in the perception of those making the reports, denote unsafe environments with exposure to violence and incidence of problems relating to the mediation of conflicts and democratic bonding. In one of the schools there is a greater emphasis on indiscipline notifications which may express, on the one hand, the attention of school professionals to events that put at risk the maintenance of authority and the fulfilment of conviviality norms in the sphere of relations between students and teachers and, on the other, the relation between students via-a-vis the established disciplinary system. In the other school there are a noteworthy number of notifications relating to the schooling routine relevant to the overall organization of the institution. The results of the research suggest the necessity for administrative departments' support so that schools in vulnerable territories are able to efficiently face situations that affect their schooling environments.